Adaptive evolution in locomotor performance: How selective pressures and functional relationships produce diversity. (1st January 2016) - Scales, Jeffrey A.; Butler, Marguerite A.
Abstract: Despite the complexity of nature, most comparative studies of phenotypic evolution consider selective pressures in isolation. When competing pressures operate on the same system, it is commonly expected that trade‐offs will occur that will limit the evolution of phenotypic diversity, however, it is possible that interactions among selective pressures may promote diversity instead. We explored the evolution of locomotor performance in lizards in relation to possible selective pressures using the Ornstein–Uhlenbeck process. Here, we show that a combination of selection based on foraging mode and predator escape is required to explain variation in performance phenotypes. Surprisingly, habitat use contributed little explanatory power. We find that it is possible to evolve very different abilities in performance which were previously thought to be tightly correlated, supporting a growing literature that explores the many‐to‐one mapping of morphological design. Although we generally find the expected trade‐off between maximal exertion and speed, this relationship surprisingly disappears when species experience selection for both performance types. We conclude that functional integration need not limit adaptive potential, and that an integrative approach considering multiple major influences on a phenotype allows a more complete understanding of adaptation and the evolution of diversity.